Developing Thai Citizenship Consciousness in Ethnic Children and Youths A Case Study of Moken Children and Youths in Koh Lao, Ranong Province - changkid, pariwat (King Prajadhipok’s Institute Journal, 2020)
The research objectives were (1) to design the model for developing consciousness of good Thai citizenship values among ethnic children and youths, a case study of Moken children and youths in Koh Lao, Ranong province, and (2) to determine outcomes from implementing the model with a target group of 30 Moken children and youths in Koh Lao. The research revealed the following. (1) The model for developing consciousness of good Thai citizenship values among Thai ethnic children and youths, a case study of Moken children and youths in Koh Lao, Pak Nam sub-district, Muang district, Ranong province, was named “Building Consciousness of Thai Citizenship Values Course.” The 48-hour course covered principles related both directly and indirectly to desirable citizen characteristics. The course topics included main forms of government in the current world, forms of government in ASEAN countries, history and forms of government in Thailand, population in democracy, Thailand’s constitution and citizenship, human rights, ethnic groups in Thailand, civic duty in Thailand, consciousness of Thai citizenship, 12 Thai core values, and self-management of community and locality. The course was divided into 12 units of four hours each. The quality assessment showed that the course had a quality score with an average of 4.73 out of 5. (2) The outcomes of the model for developing consciousness of good Thai citizenship values among Thai ethnic children and youths showed that there was consciousness of values of good citizenship at a high level. Using a 5-point Likert scale questionnaire, the children’s and youths’ satisfaction with the model was at a very good level with a mean of 4.59. The results of this research reflects that developing consciousness of Thai citizenship among children and youths of ethnic groups in different areas requires a specific model for each area should develop and the operation a curriculum for the group.